Sensor-based demand-controlled ventilation: a review - Fisk, William J. (1998)
With sensor-based demand-controlled ventilation (SBDCV), the rate of ventilation is modulated over time based on the signals from indoor air pollutant or occupancy sensors. SBDCV offers two potential advantages: better control of indoor pollutant concentrations, and lower energy use and peak energy demand. Based on theoretical considerations and on a review of literature, SBDCV has the highest potential to be cost-effective in applications with the following characteristics: (a) a single or small number of pollutants dominate so that ventilation sufficient to control the concentration of the dominant pollutants provides effective control of all other pollutants; (b) large buildings or rooms with unpredictable temporally variable occupancy or pollutant emission; and (c) climates with high heating or cooling loads or locations with expensive energy. At present, most SBDCV systems are based on monitoring and control of carbon dioxide (CO2) concentrations. There is a limited number of well-documented case studies that quantify the energy savings and the cost-effectiveness of SBDCV. The case studies reviewed suggest that in appropriate applications, SBDCV produces significant energy savings with a payback period typically of a few years.